Taxation of Offshore Indirect Transfers (OIT) in developing countries - Thurneysen, Bastian (Department of Commercial Law, 2020)
In a world of globalized capital, individuals, companies, individuals, and nations, often benefit from investment opportunities in which capital is free to flow across borders and jurisdictions with limited restrictions. Foreign direct investment in developing nations is certainly one of the perceived benefits of this milieu in which capital is liberalized, as it often provides critical funds for resource extraction, industrial growth or increased agricultural output, and, supposedly, an overall influx of positive development potential (Rixen, 2015: 325). Indeed, many developing nations work very hard to attract foreign investment capital, including through tax incentives, which can create opportunities for utilizing natural resources, employment, and infrastructure development. Overall, international investment is often portrayed as win-win scenario, with some, but few drawbacks. However, this does not mean that the international flow of capital is not without its complications. Not all pertinent actors involved in the global chains of investment, industry, and development, feel as though the international system is a level playing field for all parties. This is particularly true when it comes to the notion of taxation, which is on one hand largely a domestic issue, meaning that taxation policy is ultimately in the jurisdiction of national governments. Yet with that said, the international arena in the early part of the second millennium is a world of international business in which capital investment flows readily across and between jurisdictions, heightening the need for more robust, creative, and far-reaching policy and legislation that allows nations to capture the taxable income generated from their domestic resources in foreign destinations, because of the high degree of foreign ownership through globalized capital (Toledano, Bush, & Mandelbaum, 2017: 13). Depending on the country in question, this can be a daunting task. The reality of the international arena is one of countries that are divided across a spectrum of wealth, from a small number of very wealthy and powerful nations, (from which stem most of the powerful corporations and other investment engines), to those who struggle to meet the basic needs of their people, and to maintain stable governance. It is those nations at the lower end of the scale that are generally recognized as being the most vulnerable to powerful international forces. The economic drivers in such nations are often found in raw resources, whether in labour, mineral deposits, or agriculture, most of which rely on some degree of foreign investment both in capital and technological capacity in order to harness and extract their value (Kosters, 2004: 7). In turn, the taxes that are generated from such activity not only play a substantial role in filling the coffers of these governments, but are one of the few potential resources for meaningful earnings for the state, in countries where they are most needed, primarily for very basic needs of infrastructure and daily governance (Marais, 2018: 611). Increasingly over the past decades, it has been recognized that there is a great deal more that powerful countries and institutions can and perhaps should do in order to help the less powerful harness their wealth, from taxation and other sources (Kosters, 2004: 7). As of more recent years, various institutions have entered the fray in regard to development and related issues like taxation at the international level, operating via collective agreements. These include groups such as the Organization for Economic Cooperation and Development (OECD), International Monetary Fund (IMF), and World Bank. While several international bodies, the OECD included, provide some guidance and direction for taxation, these agreements are voluntary, and do not supersede the power or responsibility of national governments to monitor the usage, flow, and taxation of national resources. Further, there is a notable critique on the somewhat conflictual nature of these institutions, in that they get their power from the same powerful nations whose business elites have been benefiting from lopsided power dynamics on the international level all along, and in many ways, despite the good intentions of some initiatives on their part, on the whole, they continue to do so, meaning that developmental needs and the ethics of equity and fairness still must fight to be recognized against a backdrop of profiteers who are in many ways loathe to surrender their advantages, whether they are deemed to be fair or not (Marais, 2018: 612). In briefly considering the taxation landscape in regard to OITs, at present there exists a variety of approaches. On one hand there are some guidelines presented by some intergovernmental organizations, for example, the OECD, which suggests taxation of OITs in some limited cases. However, this serves as a guideline for member countries and not a regulation. It should be further noted that, regardless of policy source and orientation, any application of taxation to OITs can only occur when a nation has a suitable domestic taxation policy in place, as such taxes are ultimately under the authority of national governments where the resource resides. This has led some researchers to comment on the distinction between developed and developing nations when it comes to the value and importance of taxing OITs, whereby it may be very much in the interest of developing countries to harness the tax on this activity, and much less important for developed nations (Lau, 2015:43) . This is owing largely to the fact that such holdings and transfers by multinationals are far more common in developing nations, and to the fact that the taxes on such. This may provide a meaningful backdrop for understanding the variance in approach to OITs from nation to nation, as well as create a focal point for understanding how developing nations in particular can use taxation as one of the tools needed to harness the power of its own resources in order to better foster development.